PENGARUH KEPEMIMPINAN SPIRITUAL DAN QWL (QUALITY OF WORK LIFE) TERHADAP OCB (ORGANIZATIONAL CITIZENSHIP BEHAVIOR) YANG DIMEDIASI KOMITMEN ORGANISASI (Studi pada Guru SMP Islam Paiton dan SMP Insan Terpadu) - Ulum, Rahman; Hermawati, Adya; Nasharuddin (Jurnal Cakrawala Ilmiah, 2024)
This research aims to determine the mediating role of organizational commitment in the indirect influence of spiritual leadership and quality of work life on organizational citizenship behavior of teachers at Paiton Islamic Middle School and Insan Terpadu Middle School. The population in this study were all 56 teachers. The sample uses a saturated sampling technique because the population is relatively small. So the sample used in this research was 56 respondents. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS version 4 software. The research results show that spiritual leadership is unable to improve organizational citizenship behavior. Spiritual leadership is able to increase organizational commitment. Quality of work life is unable to improve organizational citizenship behavior. Quality of work life is able to increase organizational commitment. Organizational commitment is able to increase organizational citizenship behavior. Organizational commitment is able to play a role in mediating the indirect influence of spiritual leadership on organizational citizenship behavior. Organizational commitment is able to play a role in mediating the indirect influence of quality of work life on organizational citizenship behavior.